2021
DOI: 10.3390/ijerph18189789
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Preservation of Hard and Semi-Hard Cheeses: Quality and Safety

Abstract: Cheese is a dairy product with potential health benefits. Cheese consumption has increased due to the significant diversity of varieties, versatility of product presentation, and changes in consumers’ lifestyles. Spoilage of hard and semi-hard cheeses can be promoted by their maturation period and/or by their long shelf-life. Therefore, preservation studies play a fundamental role in maintaining and/or increasing their shelf-life, and are of significant importance for the dairy sector. The aim of this review i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 202 publications
0
9
0
Order By: Relevance
“…For instance, Ordóñez et al [ 109 ] have identified isopenty1amine, spermidine, phenylethylamine and tryptamine in Idiazabal cheese and Tofalo et al [ 110 ] have not identified HIS in Pecorino di Farindola cheese. The differences observed compared to previous studies and other raw ewe milk-derived cheeses, could be attributed, apart from the different BAs analysed, to the microbiota or to the different cheese-making or ripening parameters used by each producer [ 113 , 114 ]. Within the predominant BAs detected, information about MMA is scarce, but it has been described as harmful to livestock in high concentrations [ 115 ].…”
Section: Discussionmentioning
confidence: 58%
“…For instance, Ordóñez et al [ 109 ] have identified isopenty1amine, spermidine, phenylethylamine and tryptamine in Idiazabal cheese and Tofalo et al [ 110 ] have not identified HIS in Pecorino di Farindola cheese. The differences observed compared to previous studies and other raw ewe milk-derived cheeses, could be attributed, apart from the different BAs analysed, to the microbiota or to the different cheese-making or ripening parameters used by each producer [ 113 , 114 ]. Within the predominant BAs detected, information about MMA is scarce, but it has been described as harmful to livestock in high concentrations [ 115 ].…”
Section: Discussionmentioning
confidence: 58%
“…Packaging requirements thus vary according to the cheese type, as the maturation rate, water content and mechanical stability will depend on the composition. Nevertheless, the factors to be considered when selecting a packaging material are almost the same for all cheeses, i.e., permeability to gases, mechanical properties and transparency [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effective replacement of preservatives (e.g., sorbates, nitrites, etc.) is the focus of various studies, recently reviewed [6]. Extracts and essential oils from aromatic plants have attracted the attention of the scientific community regarding their safety as natural ingredients as well as their wide application in Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%